2016
DOI: 10.1017/s0305000916000301
|View full text |Cite
|
Sign up to set email alerts
|

Learning words from speakers with false beliefs

Abstract: During communication, hearers try to infer the speaker's intentions to be able to understand what the speaker means. Nevertheless, whether (and how early) preschoolers track their interlocutors' mental states is still a matter of debate. Furthermore, there is disagreement about how children's ability to consult a speaker's belief in communicative contexts relates to their ability to track someone's belief in non-communicative contexts. Here, we study young children's ability to successfully acquire a word from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The same findings are also significant in the context of broader debates about children's early communication skills by showing that young children are sensitive to social pragmatic reasoning in calculating speaker meaning. In this sense, they are consistent with evidence demonstrating, among other things, that preschoolers consult a speaker's knowledge when learning a novel word (Papafragou, Fairchild, Cohen, & Friedberg, 2016;Sabbagh & Baldwin, 2001) and take into account their interlocutors' perspective during online reference assignment (Nadig & Sedivy, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…The same findings are also significant in the context of broader debates about children's early communication skills by showing that young children are sensitive to social pragmatic reasoning in calculating speaker meaning. In this sense, they are consistent with evidence demonstrating, among other things, that preschoolers consult a speaker's knowledge when learning a novel word (Papafragou, Fairchild, Cohen, & Friedberg, 2016;Sabbagh & Baldwin, 2001) and take into account their interlocutors' perspective during online reference assignment (Nadig & Sedivy, 2002).…”
Section: Discussionsupporting
confidence: 87%
“…Verbs like think, know and remember refer to physically unobservable states, and relationships between their acquisition and ToM development have been reported (Moore, Pure, & Furrow, 1990; Olson, 1988). Papafragou, Fairchild, Cohen, and Friedburg (2017) found that the tracking of speakers’ mental states is used when acquiring a new word from a person, and that this ability is developing between the ages of 3 and 5. For syntax it has been argued by de Villiers (2007) that the syntax of sentence complements under certain verbs is what facilitates reasoning about the knowledge states of others, claiming that language helps the development of ToM reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found that, compared to their performance in standard FB tasks, even 3-year-olds (and older children) performed proficiently in tracking an agent's FB to assign reference in situations that involve learning of new object labels. However, a recent study by Papafragou et al [32] suggests that this effect may be an artefact of miss-matched control conditions: once both task types were closely matched, no performance-enhancing effects of word learning contexts over standard FB tasks were found.…”
Section: Introductionmentioning
confidence: 92%
“…3 that did not refer to the child's memory of previous object locations (thus did not provide a semantic shortcut). Note that we did not include the novel label for the referred object in the request, because Southgate et al's study showed that it is not necessary for infants' success (see also [32]). We coded for the box that participants approached or pointed at first, which was either the referred box (correct in TB, incorrect in FB) or the non-referred box (incorrect in TB, correct in FB).…”
Section: Sefo Taskmentioning
confidence: 99%